Rasionalisasi Tradisi Rasulan: Reinterpretasi Makna Ritual, Nilai Pendidikan Komunal, dan Negosiasi Kultural - Cut Nuraini (Universitas Indraprasta PGRI, 2026)
This study aims to examine the process of rationalizing the meanings attached to offering rituals and trance phenomena within the *Rasulan* tradition in Gunung Kidul Regency, Special Region of Yogyakarta. Specifically, the research focuses on identifying communal educational values ​​and analyzing the role of educational structures as drivers in transforming the community's mindset from a mystical-traditional outlook to a rational-religious one. The study employs a qualitative approach utilizing field research methods. Data were collected through a socio-anthropological lens involving participant observation of ritual processions, in-depth interviews with key informants (customary leaders, “modin” ritual participants, and educators), and document analysis. Data validity was verified using source and method triangulation, while data analysis applied the interactive model developed by Miles, Huberman, and Saldaña, comprising data reduction, data display, and conclusion drawing. The findings reveal a shift in the meaning of offerings: from mystical tributes intended to ward off misfortune to theological symbols of gratitude to God “sedekah bumi” earth alms and instruments of social cohesion “kembul bujana” communal feasting. Trance phenomena are no longer viewed literally as demonic possession but are rationalized as a means of collective psychological catharsis—stemming from the pressures of an agrarian economy—and as a reminder of social norms. This cultural transformation is systematically driven by three educational pillars: formal education that fosters scientific-curricular reasoning; informal education through the transmission of ethical philosophies within the family; and non-formal education via inclusive cultural outreach “dakwah” by religious leaders. Theoretically, this study contributes to reinforcing Weber’s theory of rationalization and Berger’s